Identification and in situ hybridization to mitotic chromosomes of a molecular marker linked to maleness in Anastrepha fraterculus (Wied.) - Basso, Alicia (2020)
Fil: Basso, Alicia. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Biología Aplicada y Alimentos. Cátedra de Genética. Buenos Aires, Argentina.